1986
DOI: 10.1159/000234081
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine IgE Responses with Amino Acid Polymer/Allergen Conjugates

Abstract: Conjugates of poly-N-methylglycine (polysarcosine) and grass pollen allergen extracts, which have been previously shown to suppress murine IgE responses, were examined for their ability to modify lymphocyte activity in vitro. Allergen-specific T lymphocytes obtained from Balb/c mice gave a reduced response to syngeneic accessory cells pulsed with conjugates of polysarcosine-allergen compared with the response found using equivalent concentrations of native extract. Pretreatment of accessory cells with either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Unlike F-MLP/rye conjugate, however, this material did not react with accessory cell-processed antigen cells but rather caused the in duction of suppressor cell subsets both in vivo and in vitro [4], As the induction of antigen-specific suppres sor cells may be an important requirement for the beneficial effects of allergen immunotherapy [14], the use of T' allergoid materials, such as F-MLP/rye which do not appear to alter significantly the cellular response to allergens, may be limited. One possibility, however, would be to use T' allergoids to expand the allergen-specific helper T cell pool of patients in a safe manner, and then to boost the antibody response with a small dose of unmodified allergen.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike F-MLP/rye conjugate, however, this material did not react with accessory cell-processed antigen cells but rather caused the in duction of suppressor cell subsets both in vivo and in vitro [4], As the induction of antigen-specific suppres sor cells may be an important requirement for the beneficial effects of allergen immunotherapy [14], the use of T' allergoid materials, such as F-MLP/rye which do not appear to alter significantly the cellular response to allergens, may be limited. One possibility, however, would be to use T' allergoids to expand the allergen-specific helper T cell pool of patients in a safe manner, and then to boost the antibody response with a small dose of unmodified allergen.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, IgE suppression [4], modulation of inflammatory cell movement into sites of allergen challenge [12] and the late phase reaction to allergens [1] have all been identified as possible targets for altered T cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugates of polysarcosine and allergens have been shown to suppress murine IgE antibody by Tcell mechanisms [21]. In addition other modified allergens have been described that have extensively reduced IgE-reactivities and, poor IgG-inducing pro perties, but yet have various retained T-cell-stimulating capacities in experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…[92] The reduced IgE response was transient [93] and was attributed partly to a short-lived antigen-specific T cell suppression. [94] It was further demonstrated that intranasal application of the conjugate can reduce the serum IgE antibody response that was brought about through exposure to the grass pollen extract, [95] providing a method to treat allergy. Kimura et al…”
Section: Immunogenicitymentioning
confidence: 99%